Revitalisasi Permainan Tradisional Jambi untuk Pembelajaran Fisika Kontekstual: Kajian Efektivitas Melalui Rasch Model - Cindy Aulia Phadila; Yunita; Eka Metha Natalia; Intan Permatasari; Shifa Azzara Chairunnisa; Wawan Kurniawan; Nuri Istifah Khasanah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Physics is often perceived as difficult and abstract because learning activities are rarely connected to students’ real-life and cultural experiences. This study aimed to analyze the validity and reliability of assessment instruments using the Rasch Model, evaluate the effectiveness of a game-based physics learning module grounded in Jambi traditional games, and examine students’ motivation and responses. A quantitative Research and Development (R&D) approach based on the ADDIE model was employed involving 68 eleventh-grade science students. Data were collected through pretest–posttest assessments, motivation questionnaires, and classroom observations, then analyzed using the Rasch Model and paired-sample t-test. The findings showed high instrument quality, with person reliability ranging from 0.85–0.87 and item reliability from 0.92–0.93. Most items met the Rasch fit criteria (Infit–Outfit MNSQ 0.5–1.5), indicating valid and consistent measurement. Students’ mean scores improved significantly from 52.3 to 83.7, with a very large effect size (Cohen’s d = 1.85). Rasch analysis also revealed a positive shift in students’ conceptual abilities and showed that approximately 75% of students achieved above-average motivation after the intervention. These findings indicate that integrating Jambi traditional games into physics learning effectively contextualizes abstract concepts, enhances conceptual understanding, motivation, and creates more meaningful learning experiences.